2021
DOI: 10.1186/s12864-021-08014-1
|View full text |Cite
|
Sign up to set email alerts
|

Female developmental environment delays development of male honeybee (Apis mellifera)

Abstract: Background Nutrition and cell size play an important role in the determination of caste differentiation in queen and worker of honeybees (Apis mellifera), whereas the haploid genome dominates the differentiation of drones. However, the effects of female developmental environment on the development of males remain unclear. In this study, young drone larvae were transferred into worker cells (WCs) or remained in drone cells (DCs) to rear drones. The drone larvae were also grafted into queen cells… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Used the 2 −ΔΔCt method to calculate the above DEcircRNAs’ relative expression level ( Livak and Schmittgen, 2001 ). Based on the method described by Liu et al (2021) , the data were presented as the mean ± standard deviation (SD) and analyzed with two-sided Student’s t-test utilizing the Graph Prism eight software (ns p > 0.05; * p < 0.05; ** p < 0.01; *** p < 0.001).…”
Section: Methodsmentioning
confidence: 99%
“…Used the 2 −ΔΔCt method to calculate the above DEcircRNAs’ relative expression level ( Livak and Schmittgen, 2001 ). Based on the method described by Liu et al (2021) , the data were presented as the mean ± standard deviation (SD) and analyzed with two-sided Student’s t-test utilizing the Graph Prism eight software (ns p > 0.05; * p < 0.05; ** p < 0.01; *** p < 0.001).…”
Section: Methodsmentioning
confidence: 99%
“…The relative expression of the above DElncRNAs was calculated using the 2 -∆∆Ct method [77]. According to the described method by Wan et al [78] and Liu et al [79], the data are shown as the means ± standard deviation (SD) and were subjected to Student's t-test by using the Graph Prism 8 software (ns, p > 0.05; *, p < 0.05; **, p < 0.01; ***, p < 0.001).…”
Section: Rt-qpcr Validationmentioning
confidence: 99%